Determinants of Profit Forecast by Analysts Tunisians - Boudiche, Myriam (Journal of Asian Business Strategy, 2013)
This article aims to highlight the degree of suitability of the information issued in the annual report with the conception of the usefulness of 49 volunteers and forecast information by Tunisian financial analysts. Our questionnaire with 50 financial Tunisian analysts aims to analyze the degree of utility they provide to forecast and voluntary information published in the annual reports of 50 companies quoted in the stock exchange of Tunis (Tunis Stock Exchange) in 2010. Our results highlight the existence of a significant gap between information supply and demand. More specifically, the supply of 12 items is completely different from their request by the Tunisian financial analysts.